Profile of Phenolic Acids and Flavonoids of Red Beet and Its Fermentation Products. Does Long-Term Consumption of Fermented Beetroot Juice Affect Phenolics Profile in Human Blood Plasma and Urine? - Natalia Płatosz; Tomasz Sawicki; Wiesław Wiczkowski (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to determine the profile of phenolic acids and flavonoids in red beetroot products and these compounds fate in the human body after long-term exposure to fermented red beet juice. Phenolic acids and flavonoids were analyzed by HPLC-MS/MS. The performed analysis revealed that beetroot and its products were the notable sources of phenolic acids and flavonoids, with isoferulic acid, protocatechuic acid, epicatechin, and apigenin predominating among the twenty compounds detected. However, the compounds analyzed appeared mainly in the bound form in the fresh material. The results obtained indicate that the fermentation process caused an increase in the content of free phenolic acids and reduced the content of conjugated phenolic acids. Contrarily to phenolic acids, the same process caused a reduction in the content of free flavonoids and an increase in the content of conjugated flavonoids. Moreover, the 14-day spontaneous fermentation process resulted in a significant reduction (by 45.18%) in the total content of phenolics (phenolic acids and flavonoids). However, it was observed that forty-two days of the regular intake of the fermented beetroot juice (200 mL/60 kg body weight) generally did not affect concentrations of phenolic acids and flavonoids in the volunteers' body fluids compared to their concentrations in fluids before fermented beetroot juice consumption.